Chemical effect on K shell X-ray fluorescence parameters for some Mn and Ni compounds - Turhan, Mehmet Fatih; Turşucu, Ahmet; Akman, Ferdi; Akdemir, Fatma; Durak, Rıdvan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Kα, Kβ and total K X-ray fluorescence cross-sections, K shell fluorescence yields, Kβ/Kα X -ray intensity ratios, K to L shell vacancy transfer probabilities and Auger electrons emission ratios of some selected Mn and Ni compounds have been investigated. The measurements were carried out by using Am-241 radioactive source and highresolution Si(Li) detector. The measured results were compared with other experimental values and theoretical calculations. Our values are in good concordance with calculated theoretical and other experimental values.
Keywords: K X-ray production cross-section; Intensity ratio; K shell fluorescence yield; K to L shell vacancy transfer probabilities